Effect of amino acid-enriched nutrient solutions on early growth of tomato and scarlet eggplant - Lisboa, Lucas Aparecido Manzani; Borge, Erik Cícero Santos; Borge, Éder Cícero Santos; Santirso, Brunno de Oliveira; Oliveira, Igor Renato da Costa de; Martins, Fabielli Souza Leite (Brazilian Journal of Science, 2025)
Extensive vegetable cultivation requires large areas and labor, increasing production costs. An alternative is hydroponic production, where the plant receives all the nutrients in the necessary concentrations to complete its entire cycle. This study aims to evaluate the initial development of tomato and scarlet eggplant grown in a nutrient solution containing different amino acids. Two simultaneous experiments were conducted in April 2024 at the Andradina Educational Foundation, located in the municipality of Andradina, São Paulo state. The experimental design was completely randomized (CRD). Tomato plants (Solanum lycopersicum L.) and scarlet eggplant (Solanum aethiopicum gr. Scarlet eggplant) were grown in a nutrient solution containing amino acids: (Control) no amino acids, Tryptophan, Lysine, Cysteine, Phenylalanine and all amino acids, comprising six treatments, with four replicates totaling 24 plots. Each plot consisted of one seedling, and the concentration of each amino acid was 10 mg L-1 of nutrient solution. Tomatoes responded better to the presence of amino acids in the nutrient solution. The combination of the amino acids tryptophan, lysine, cysteine, and phenylalanine resulted in enhanced tomato and scarlet eggplant development when grown in nutrient solution. The use of amino acids in nutrient solution may be an alternative to improving the initial development parameters of tomatoes and scarlet eggplant. Lysine and phenylalanine supplementation improved tomato early growth and nitrogen assimilation, while scarlet eggplant responses were moderate. Further studies should evaluate long-term yield and economic feasibility.